JOB MARKET PREPARATION AND JOB PERFORMANCE, GRADUATE PERCEPTION VERSUS MARKET REALITIES IN THE CASE OF INSTITUTE OF BUSINESS ADMINISTRATION SUKKUR - Shaikh, Faiz M.; Gopang, Nazir Ahmed (Journal of European Economy, 2017)
A survey of different organizations, firms identifies characteristics associated with above average starting salary offers in allied fields of, management sciences, business and economics. A complementary survey made by the students at IBA_Sukkur-Sindh from – 1995–2007–08 batches, data were collected from 100students and 50 organizations and firms respondents by using simple random technique. Results showed that firms value work experience and leadership experience more than students do, where as student’s value raising grade point average and interview preparation more than do firms. Students seeking a firm’s maximum starting salary offers will need to enhance academic performance with substantial work experience and leadership experience. It was revealed that leadership qualities and job performance and GPA were not correlated. It was revealed that the faculty and teaching methodology and technology all they are positively associated with the student’s performance.